Perancangan Website Pendataan Stok Barang pada Ud Chandra Menggunakan Metode Rapid Application Development (RAD) - Sugiarto Aryatama; Furqan Khalidy; M.Khaibar Putra Adithia (KAMPUS AKADEMIK PUBLISING, 2026)
Inventory management at UD Chandra is currently still carried out conventionally, through manual record-keeping and the use of simple, non-integrated spreadsheets. This causes various operational problems, such as a high risk of human error, inaccurate stock data, slow report generation processes, and difficulty for the owner in monitoring product availability in real time. On the other hand, customers also face obstacles in obtaining product availability information because they have to contact the store directly. This research aims to design and build a website-based inventory data recording information system to optimize inventory management and improve information transparency for customers. The system development method used is Rapid Application Development (RAD), chosen because it emphasizes development speed, flexibility, and intensive user involvement through the stages of requirement planning, design workshop, and implementation. The result of this research is a website-based platform that provides features for item data management, recording of incoming and outgoing transactions, automatic stock reports, low-stock notifications, and a product catalog for customers. The implementation of this system is expected to improve operational efficiency, data accuracy, and the quality of strategic decision-making for business owners, as well as provide easier access to information for UD Chandra's customers.